Postbiotic studies of mixed cultures of Schleiferilactobacillus harbinensis LH991 and Pichia kudriavzevii B-5P produced by in vitro rumen producing short-chain fatty acid - Yetti Marlida; Tan Joo Shun; Syofyan Syofyan; Laily Rinda Ardani; Lili Anggraini (Veterinary World, 2024)
Background and Aim: Postbiotics are functional bioactive compounds or bioactive molecules with beneficial effects on health and functional activities in humans or livestock, produced by probiotic bacteria or yeast. Several postbiotics, including enzymes, short-chain fatty acids, amino acids, extracellular polysaccharides, microbial cell fragments, and teichoic acids, are currently being widely studied. This study aimed to explore the potential of secondary metabolites of Schleiferilactobacillus harbinensis LH 991 and Pichia kudriavzevii B-5P as lactic acid bacteria (LAB) and yeast isolated from Budu (fermented fish) which can act as postbiotics through in vitro rumen fermentation.